2008
DOI: 10.2139/ssrn.967303
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Estimation of High Frequency Jump Diffusions with Microstructure Noise and Stochastic Volatility

Abstract: When analysing the volatility related to high frequency financial data, mostly nonparametric approaches based on realised or bipower variation are applied. This article instead starts from a continuous time diffusion model and derives a parametric analog at high frequency for it, allowing simultaneously for microstructure effects, jumps, missing observations and stochastic volatility.Estimation of the model delivers measures of daily variation outperforming their nonparametric counterparts. Both with simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Periodicity estimates have been used for disentangling the periodic variation in volatility and the impact of news on intraday volatility (Andersen et al, 2003;Dominguez and Panthaki, 2006), forecasting of intraday variance (Martens et al, 2002) and efficient estimation of daily volatility using high-frequency returns (Areal and Taylor, 2002;Bos, 2008). For all these applications, it is natural to use a jump-robust periodicity estimate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodicity estimates have been used for disentangling the periodic variation in volatility and the impact of news on intraday volatility (Andersen et al, 2003;Dominguez and Panthaki, 2006), forecasting of intraday variance (Martens et al, 2002) and efficient estimation of daily volatility using high-frequency returns (Areal and Taylor, 2002;Bos, 2008). For all these applications, it is natural to use a jump-robust periodicity estimate.…”
Section: Resultsmentioning
confidence: 99%
“…If there are jumps, more observations are downweighted. The WSD in (2.12) has a 69% efficiency under normality of the r i s, as opposed to the 37% efficiency of the ShortH (see Boudt et al, 2008, for details).…”
Section: Non-parametric Estimation Of Periodicitymentioning
confidence: 99%
“…Moreover, realized jumps can provide an insight into the nature of jumps for asset classes or common movements (co-jumps) between assets, see Lahaye, Laurent, and Neely (2009). Parametric methods to test for jumps are adapted by Duan and Fülöp (2007) and Bos (2008) where jumps are detected as part of the estimation method. Boudt et al (2008) have shown that pronounced intraday periodicity leads to the distorted jump inference based on the Lee and Mykland (2008) test.…”
Section: Introductionmentioning
confidence: 99%
“…Andersen and Bollerslev (1997b) and Andersen et al (2007a) document the importance of allowing for jumps and for periodicity of intraday volatility in the nonparametric estimation and forecasting of volatility, but treat these two features separately. Periodicity estimates that are robust to price jumps are needed for disentangling the periodic variation in volatility and the impact of news on intraday volatility (Dominguez and Panthaki, 2006), forecasting of intraday variance (Martens et al, 2002), efficient estimation of daily volatility using high-frequency returns (Areal and Taylor, 2002;Bos, 2008) and, as we show in this paper, for intraday jump detection.…”
Section: Introductionmentioning
confidence: 89%